N-phenyl phenothiazine super-crosslinked polymer catalyst as well as preparation method and application thereof
6-difluoromethylphenylphenylidene was successfully synthesized by catalyzing the reaction of difluoromethyltriphenylphosphine bromide and 2-isocyanobiphenyl compounds using N-phenylphenylazine supercrosslinked polymer catalysts. Derivatives solve the high cost and non-reusable problems of traditional catalysts, and achieve efficient and environmentally friendly photocatalytic synthesis.
Patent Information
- Application Number
- CN202411375917.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing photocatalytic technology, traditional homogeneous catalysts have problems such as expensive, easy metal residue, poor stability, difficult product purification, and limited reusability, which limits their wide application in organic synthesis.
Using N-phenylphenthiazine supercrosslinked polymer as a catalyst, a three-dimensional network-like porous structure supercrosslinked polymer material was prepared by Friedel-Crafts reaction, which was used to catalyze difluoromethyltriphenylphosphine bromide and 2 -Tandem fluoroalkylation cyclization reaction of -isocyanobiphenyl compounds is synthesized to synthesize 6-difluoromethylphenanthine derivatives.
It realizes photocatalytic synthesis with mild conditions, simple operation, high reaction yield, recyclable catalyst, few waste, low cost and environmentally friendly, and is suitable for industrial production applications.
Smart Images

Figure CN119456028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an N-phenylphenothiazine hyper-crosslinked polymer catalyst and a preparation method thereof and application of the catalyst in catalyzing the synthesis of 6-difluoromethylphenanthridine derivatives, belonging to the technical field of photocatalysis. Background Art
[0002] In recent years, in order to solve the problems of large amount of energy consumption and release of pollutants in traditional organic conversion processes, photocatalytic organic synthesis using light energy, a clean energy, has emerged. Traditional homogeneous catalysts, represented by transition metal complexes and organic dyes, have been widely used in photocatalytic organic synthesis and have shown excellent catalytic activity and high conversion rate. However, their high price, easy metal residue, poor stability, difficulty in product purification, and limited reusability have hindered their large-scale practical application in organic synthesis. In comparison, organic semiconductor materials represented by insoluble metal-organic frameworks and carbon nitride have great potential in non-phase photocatalytic reactions because of their advantages such as simple separation and recyclability. However, these materials also have the disadvantages of narrow light absorption range, susceptibility to photocorrosion, cumbersome structural modification, and easy recombination of photogenerated carriers, and their performance in photocatalytic applications is often insufficient.
[0003] Phenanthridine is an important branch of nitrogen-containing compounds. It is widely present in the core structure of most anticancer drugs and has a wide range of biological activities such as antibacterial, anti-tuberculosis, and anti-tumor properties, so it has important application value. In recent years, the construction of phenanthridine compounds and the functionalization modification of C-6 have become a hot topic of research. In recent years, a variety of methods have been developed to construct 6-position difluoromethyl-substituted phenanthridine compounds using difluoromethanesulfinyl chloride, diaryl (difluoromethyl) sulfonium salts, and difluoromethyl sulfone compounds as difluoromethyl donors through photocatalytic free radical tandem cyclization reactions. For example, in 2015, a research group reported the use of 2-isocyanobiphenyl as a raw material, Ir(ppy)3 as a photocatalyst, sodium carbonate as an alkaline additive, and difluoromethanesulfenyl chloride to react at room temperature to prepare 6-difluoromethylphenanthridine (Org. Lett., 2015, 17, 4401-4403.); in 2016, a research group reported the use of 2-isocyanobiphenyl as a raw material, Ru(bpy)3Cl2 as a photocatalyst, sodium carbonate as an alkaline additive, and difluoromethyl (2-benzothiazolyl) sulfone at room temperature. 6-difluoromethylphenanthridine was prepared by the following reaction (Angew.Chem.Int.Ed.,2016,55,2743-2747.); In 2020, a research group reported the use of 2-isocyanobiphenyl as a raw material, Ir(ppy)3 as a photocatalyst, potassium hydroxide as an alkaline additive, and (difluoromethyl)phenyl(2,4,6-trimethoxyphenyl)sulfonium tetrafluoroborate at room temperature to react and prepare 6-difluoromethylphenanthridine (J.Org.Chem.,2020,85,10479-10487.). The above method requires expensive and difficult to recover metal photocatalysts, excess additives, or oxidants. Obviously, from the perspective of green chemistry, these limiting factors will hinder the widespread application of the above reaction.
[0004] It can be seen from the above that: with the continuous development of chemical technology, the field needs to develop a catalyst that is simple to prepare, low in cost, green and environmentally friendly, and has high catalytic activity to replace traditional homogeneous photocatalysts or oxidants to synthesize 6-difluoromethylphenanthridine derivatives. The present invention uses a heterogeneous catalyst N-phenylphenothiazine hypercrosslinked polymer to catalyze difluoromethyltriphenylphosphine bromide and 2-isocyanobiphenyl compounds to carry out a tandem fluoroalkylation cyclization reaction under photocatalytic conditions to synthesize 6-difluoromethylphenanthridine derivatives in one step, which has the advantages of mild conditions, simple operation, high reaction yield, recyclable catalyst, less three wastes, low cost, and environmental friendliness. Summary of the invention
[0005] One object of the present invention is to provide a N-phenylphenothiazine hypercrosslinked polymer catalyst and a preparation method thereof. Another object of the present invention is to provide the application of the above catalyst in the catalytic synthesis of 6-difluoromethylphenanthridine derivatives, thereby improving the deficiencies and defects in the prior art.
[0006] The technical solution of the present invention is as follows:
[0007] The N-phenylphenothiazine hyper-crosslinked polymer catalyst is characterized by being a hyper-crosslinked polymer material with a three-dimensional network-like porous structure prepared by Friedel-Crafts reaction using N-phenylphenothiazine shown in formula I and dimethylformal shown in formula II as raw materials.
[0008]
[0009] The N-phenylphenothiazine hyper-crosslinked polymer catalyst is characterized in that the powder X-ray diffraction spectrum of the N-phenylphenothiazine hyper-crosslinked polymer catalyst has no sharp diffraction peaks, indicating a lack of crystallinity.
[0010] The N-phenyl phenothiazine hypercrosslinked polymer catalyst is characterized in that: the N2 isothermal adsorption-desorption curve and the pore size distribution diagram show that its specific surface area is 305m 2 g -1 , the pore size is about 2 to 4 nm.
[0011] The N-phenylphenothiazine hypercrosslinked polymer catalyst is characterized in that: the Fourier transform infrared spectrum shows that its characteristic peak position is 2920cm -1 、1600cm -1 、1470cm -1 and 1258cm -1 Place.
[0012] The N-phenylphenothiazine hypercrosslinked polymer catalyst is characterized in that: 13 The C CP / MAS NMR spectrum showed that its characteristic peak chemical shifts were at 110ppm-150ppm, 55ppm and 40ppm.
[0013] The N-phenylphenothiazine hyper-crosslinked polymer catalyst is characterized in that a thermogravimetric analysis curve shows a weight loss of 26.0-26.5% at 200-800°C.
[0014] The present invention also provides a method for preparing an N-phenylphenothiazine hyper-crosslinked polymer catalyst, comprising the following steps: utilizing a Friedel-Crafts reaction to disperse N-phenylphenothiazine, dimethylol formal and Lewis acid in a solvent, stirring and reacting at 60 to 120° C. for 12 to 36 hours, cooling and filtering, washing the filter cake with ethyl acetate, dichloromethane and methanol, and then heating and refluxing extraction with methanol in a Soxhlet extractor for 12 to 24 hours, cooling and filtering again, and drying the obtained solid to obtain an N-phenylphenothiazine hyper-crosslinked polymer catalyst.
[0015] Furthermore, the molar ratio of N-phenylphenothiazine to dimethylol formal is 1.0:2.0-6.0, the molar ratio of N-phenylphenothiazine to Lewis acid is 1.0:5.0-10.0, and the Lewis acid is selected from at least one of titanium tetrachloride, ferric chloride, aluminum chloride, tin tetrachloride, boron trifluoride, iron trifluoromethanesulfonate, and lanthanum trifluoromethanesulfonate.
[0016] Furthermore, the solvent is selected from at least one of dichloromethane, chloroform, toluene, 1,2-dichloroethane, tetrahydrofuran, 1,4-dioxane, ethanol, and dimethyl sulfoxide, and the dispersion concentration of the N-phenylphenothiazine in the solvent is 0.01-0.1 mol / L.
[0017] The present invention also provides an application of the N-phenylphenothiazine hyper-crosslinked polymer catalyst, wherein the catalyst is used to catalyze the reaction of a 2-isocyanobiphenyl compound as shown in formula III and difluoromethyltriphenylphosphonium bromide as shown in formula IV to synthesize a 6-difluoromethylphenanthridine derivative as shown in formula V;
[0018]
[0019] In Formula III and Formula V, the substituent R 1 , R 2 Each is independently selected from H, C1-C10 alkyl, halogen, C1-C10 alkoxy or aryl, the aryl is selected from phenyl or substituted phenyl, and the substituent on the phenyl ring of the substituted phenyl is C1-C10 alkyl, halogen or C1-C10 alkoxy.
[0020] The application method of the catalyst of the present invention is as follows: 2-isocyanobiphenyl compounds shown in formula III, difluoromethyltriphenylphosphonium bromide shown in formula IV and the catalyst are dispersed in a reaction solvent to obtain a reaction solution, and the reaction solution is stirred at 10° C. to 40° C. for 8 to 24 hours under irradiation with a 10-30 W light source, wherein the light source is purple light, blue light or white light, and the reaction is carried out after the reaction is completed, and a 6-difluoromethylphenanthridine derivative shown in formula (V) is obtained through post-treatment.
[0021] Furthermore, the molar ratio of the 2-isocyanatobiphenyl compound shown in formula III to the difluoromethyltriphenylphosphonium bromide shown in formula IV is 1.0:1.0-3.0, and the ratio of the amount of the 2-isocyanatobiphenyl compound shown in formula III to the mass of the catalyst is 1:15-50, the unit of the amount of the substance is mol, and the unit of mass is g.
[0022] Furthermore, in the application method of the catalyst of the present invention, the reaction solvent is selected from one or a combination of any of tetrahydrofuran, dichloromethane, acetone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, and the dispersion concentration of the 2-isocyanobiphenyl compound shown in formula III in the reaction solvent is 0.05-0.2 mol / L.
[0023] Furthermore, after the reaction is completed, the post-treatment steps are as follows: the reaction solution is washed with water, extracted with ethyl acetate, the organic layers are combined, dried over anhydrous Na2SO4 and concentrated under reduced pressure, and separated by column chromatography (the eluent ratio is petroleum ether: ethyl acetate = 150:1 to 25:1, volume ratio) to obtain the target product.
[0024] By adopting the above technology, compared with the prior art, the present invention has the following significant beneficial effects:
[0025] 1) The N-phenylphenothiazine hyper-crosslinked polymer catalyst provided by the present invention is prepared in a one-pot process using cheap and readily available N-phenylphenothiazine and dimethylol formal as raw materials to form a hyper-crosslinked polymer material with a three-dimensional network-like porous structure, with low preparation cost and simple post-processing.
[0026] 2) The polymer catalyst provided by the present invention can efficiently convert 2-isocyanobiphenyl compounds and difluoromethyltriphenylphosphonium bromide into 6-difluoromethylphenanthridine derivatives under photocatalytic conditions. Compared with the traditional process, it avoids the use of metal catalysts, additives and oxidants, has the advantages of mild conditions, simple operation, high reaction yield, recyclable catalyst, less waste, low cost, environmental friendliness, etc., and is suitable for industrial production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Powder X-ray diffraction (PXRD) spectrum of the N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Example 1.
[0028] Figure 2 N2 isothermal adsorption-desorption curve of the N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Example 1.
[0029] Figure 3 Pore size distribution diagram of the N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Example 1.
[0030] Figure 4 It is the Fourier transform infrared (FT-IR) spectrum of the N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Examples 1-5.
[0031] Figure 5 Solid state of N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Example 1 13 C CP / MAS NMR spectrum.
[0032] Figure 6 Thermogravimetric analysis (TGA) curve of the N-phenylphenothiazine hyper-crosslinked polymer catalyst prepared in Example 1.
[0033] Figure 7 This is the X-ray photoelectron spectrum (XPS) of the N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Example 1.
[0034] Figure 8 This is a scanning electron microscope (SEM) image of the N-phenylphenothiazine hypercrosslinked polymer catalyst prepared in Example 1.
[0035] Fig. 9 A diagram showing the effect of recycling catalysis of the N-phenylphenothiazine hyper-crosslinked polymer catalyst prepared in Example 1. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the embodiments, so that the professional and technical personnel in the field can more fully understand the present invention, but the scope of the present invention is not limited in any way. It is well known to those skilled in the art that due to the existence of objective factors such as sample preparation, sample purity, instrument conditions and other experimental conditions, the experimental results obtained will have certain errors.
[0037] Example 1 Preparation of N-phenylphenothiazine hypercrosslinked polymer catalyst
[0038] N-phenylphenothiazine (4 mmol), anhydrous aluminum chloride (20 mmol), dimethylformal (12 mmol) were added to a 250 mL flask equipped with a magnetic rod, and 80 mL of 1,2-dichloroethane was added as a solvent, and the mixture was stirred and heated at 80°C for 12 hours. After the reaction, the reaction solution was cooled to room temperature and filtered. The solid was washed with ethyl acetate, dichloromethane, and methanol in sequence, and then heated and refluxed with methanol in a Soxhlet extractor for 24 hours, filtered, and the obtained solid was vacuum dried to obtain N-phenylphenothiazine hypercrosslinked polymer (894 mg) having the following properties: Figure 1 The PXRD spectrum is shown in Figure 1, and its N2 isothermal adsorption-desorption curve is shown in Figure 2. Figure 2 , pore size distribution diagram see Figure 3 , FT-IR spectrum see Figure 4 , solid state 13C CP / MAS NMR spectrum is shown in Figure 5 , TGA curve see Figure 6 , XPS spectrum see Figure 7 From the XPS graph, it can be seen that the chemical element composition of the catalyst is carbon, hydrogen, oxygen, nitrogen, and sulfur. Figure 8 From the SEM image, it can be seen that the catalyst has a three-dimensional porous structure. The effect of recycling catalysis is shown in Fig. 9 .
[0039] The N2 isothermal adsorption-desorption curve and pore size distribution diagram show that its specific surface area is 305m 2 g -1 The pore size is 2-4 nm; the Fourier transform infrared spectrum shows that its characteristic peak position is 2920 cm -1 、1600cm -1 、1470cm -1 and 1258cm -1 Solid 13 The CCP / MAS nuclear magnetic resonance spectrum shows that the chemical shifts of its characteristic peaks are at 110ppm-150ppm, 55ppm and 40ppm; the thermogravimetric analysis curve shows that the weight loss is 26.0-26.5% at 200-800°C.
[0040] Example 2 Preparation of N-phenylphenothiazine hypercrosslinked polymer catalyst
[0041] N-phenylphenothiazine (4 mmol), anhydrous ferric chloride (36 mmol), dimethylformal (24 mmol) were added to a 250 mL flask equipped with a magnetic rod, and 60 mL of dimethyl sulfoxide was added as a solvent, and the mixture was stirred and heated at 120°C for 24 hours. After the reaction, the reaction solution was cooled to room temperature and filtered. The solid was washed with ethyl acetate, dichloromethane, and methanol in sequence, and then heated and refluxed with methanol in a Soxhlet extractor for 18 hours, filtered, and the obtained solid was vacuum dried to obtain N-phenylphenothiazine hypercrosslinked polymer (784 mg), and its FT-IR spectrum is shown in Figure 4 .
[0042] Example 3 Preparation of N-phenylphenothiazine hypercrosslinked polymer catalyst
[0043] N-phenylphenothiazine (4 mmol), anhydrous ferric chloride (40 mmol), dimethylformal (8 mmol) were added to a 250 mL flask equipped with a magnetic rod, and 120 mL 1,4-dioxane was added as a solvent, and the mixture was stirred and heated at 100 ° C for 36 hours. After the reaction, the reaction solution was cooled to room temperature and filtered. The solid was washed with ethyl acetate, dichloromethane, and methanol in sequence, and then heated and refluxed with methanol in a Soxhlet extractor for 12 hours, filtered, and the obtained solid was vacuum dried to obtain N-phenylphenothiazine hypercrosslinked polymer (557 mg), and its FT-IR spectrum is shown in Figure 4 .
[0044] Example 4 Preparation of N-phenylphenothiazine hypercrosslinked polymer catalyst
[0045] N-phenylphenothiazine (4 mmol), tin tetrachloride (36 mmol), dimethylformal (24 mmol) were added to a 250 mL flask equipped with a magnetic rod, and 100 mL of ethanol was added as a solvent, and the mixture was stirred and heated at 80°C for 24 hours. After the reaction, the reaction solution was cooled to room temperature and filtered. The solid was washed with ethyl acetate, dichloromethane, and methanol in sequence, and then heated and refluxed with methanol in a Soxhlet extractor for 16 hours, filtered, and the obtained solid was vacuum dried to obtain N-phenylphenothiazine hypercrosslinked polymer (704 mg), and its FT-IR spectrum is shown in Figure 4 .
[0046] Example 5 Preparation of N-phenylphenothiazine hypercrosslinked polymer catalyst
[0047] N-phenylphenothiazine (4 mmol), iron trifluoromethanesulfonate (20 mmol), and dimethylformal (24 mmol) were added to a 250 mL flask equipped with a magnetic rod, and 80 mL of tetrahydrofuran was added as a solvent, and the mixture was stirred and heated at 60°C for 24 hours. After the reaction, the reaction solution was cooled to room temperature and filtered. The solid was washed with ethyl acetate, dichloromethane, and methanol in sequence, and then heated and refluxed with methanol in a Soxhlet extractor for 24 hours, filtered, and the obtained solid was vacuum dried to obtain N-phenylphenothiazine hypercrosslinked polymer (489 mg), and its FT-IR spectrum is shown in Figure 4 .
[0048] The FT-IR spectra of the N-phenylphenothiazine hypercrosslinked polymer catalysts of Examples 1-5 are compared in Figure 4 From the FT-IR graph, it can be seen that the characteristic peak positions of the catalyst materials prepared in Examples 1 to 5 are the same, and it can be considered that the materials prepared in Examples 1 to 5 have the same structure.
[0049] In addition, the samples prepared in Examples 2 to 5 have the same or similar PXRD spectra, N2 isothermal adsorption-desorption curves, pore size distribution diagrams, FT-IR spectra, solid 13 The C CP / MAS nuclear magnetic resonance spectrum, TGA curve, XPS spectrum, SEM image, and the effect of recycling catalysis indicate that the samples prepared in Examples 2 to 5 and Example 1 are the same polymer material.
[0050] Application Example 1 Preparation of 6-(difluoromethyl)phenanthridine
[0051]
[0052] To a 10 mL Schlenk tube equipped with a magnet, compound 2-isocyanobiphenyl (0.2 mmol), difluoromethyltriphenylphosphine bromide (0.2 mmol), and the N-phenylphenothiazine hypercrosslinked polymer (3 mg) prepared in Example 1 were added respectively, and 2 mL of dimethyl sulfoxide was added to the mixture as a solvent. Under 20 W blue light irradiation, the reaction was stirred at 25 ° C for 12 hours. The reaction solution was washed with water and extracted with ethyl acetate. The combined organic layers were dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 150:1, v / v), 40.3 mg of a white solid was obtained, with a yield of 88% and a melting point of 87-89 ° C.
[0053] 1 H NMR(400MHz,Chloroform-d)δ8.74(d,J=8.4Hz,1H),8.66(d,J=7.6Hz,2H),8.29(dd, J=7.4,2.0Hz,1H),7.97(t,J=7.7Hz,1H),7.88–7.77(m,3H),7.12(t,J=54.4Hz,1H); 13 C NMR(101MHz,Chloroform-d)δ151.45(t,J=26.5Hz),142.45,133.91,131.37,130.65,129.21, 128.83,128.76,127.92,126.57(t,J=4.3Hz),125.07,122.51,122.26,118.43(t,J=243.5Hz); 19 F NMR(376MHz,Chloroform-d)δ-110.53.
[0054] Application Example 2 Preparation of 6-(difluoromethyl)-8-methoxyphenanthridine
[0055]
[0056] 2-isocyanate-4'-methoxy-1,1'-biphenyl (0.2 mmol), difluoromethyltriphenylphosphonium bromide (0.2 mmol), and N-phenylphenothiazine hypercrosslinked polymer (5 mg) prepared in Example 2 were added to a 10 mL Schlenk tube equipped with a magnet, and 2 mL of N,N-dimethylacetamide was added to the mixture as a solvent. The mixture was stirred at 35° C. for 24 hours under 10 W purple light irradiation. The reaction solution was washed with water and extracted with ethyl acetate. The combined organic layers were dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 25:1, v / v), 42.5 mg of a white solid was obtained with a yield of 82% and a melting point of 126-128° C.
[0057] 1 H NMR(600MHz,Chloroform-d)δ8.55(d,J=9.1Hz,1H),8.50–8.47(m,1H),8.21–8.16(m,1H),7.93– 7.88(m,1H),7.75–7.70(m,2H),7.52(dd,J=9.1,2.5Hz,1H),7.05(t,J=54.4Hz,1H),4.02(s,3H); 13 C NMR(151MHz,Chloroform-d)δ158.76,150.29(t,J=26.4Hz),141.56,130.42,128.57,128.19,127 .96,125.03,123.86,123.68(t,J=4.3Hz),122.28,121.56,118.57(t,J=243.3Hz),105.87,55.47; 19 FNMR(565MHz,Chloroform-d)δ-111.42.
[0058] Application Example 3 Preparation of 6-(difluoromethyl)-8-phenylphenanthridine
[0059]
[0060] 2-isocyanate-1,1':4',1'-terphenyl (0.2 mmol), difluoromethyltriphenylphosphonium bromide (0.3 mmol), and N-phenylphenothiazine hypercrosslinked polymer (10 mg) prepared in Example 3 were added to a 10 mL Schlenk tube equipped with a magnet, and 2 mL of N,N-dimethylacetamide was added to the mixture as a solvent. The mixture was stirred at 10° C. for 8 hours under 30 W purple light irradiation. The reaction solution was washed with water and extracted with ethyl acetate. The combined organic layers were dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 150:1, v / v), 55.5 mg of a white solid was obtained with a yield of 91% and a melting point of 129-131° C.
[0061] 1 H NMR(600MHz,Chloroform-d)δ8.80(d,J=2.1Hz,1H),8.73(d,J=8.6Hz,1H),8.61(dd,J=7.7,1.8Hz,1H),8.23(dd,J=7.6,1.8 Hz,1H),8.16(dd,J=8.6,1.9Hz,1H),7.83–7.75(m,4H),7.57(t,J=7.7Hz,2H),7.48(t,J=7.4Hz,1H),7.09(t,J=54.4Hz,1H); 13 CNMR(151MHz,Chloroform-d)δ151.58(t,J=26.5Hz),142.54,140.74,140.14,132.91,130.76,130.61,129.23, 129.16,128.85,128.19,127.65,124.95,124.45(t,J=4.2Hz),123.10,122.97,122.29,118.62(t,J=243.5Hz); 19 F NMR(565MHz,Chloroform-d)δ-110.43.
[0062] Application Example 4 Preparation of 6-(difluoromethyl)-8-fluorophenanthridine
[0063]
[0064] To a 10 mL Schlenk tube equipped with a magnet, 4'-fluoro-2-isocyanate-1,1'-biphenyl (0.2 mmol), difluoromethyltriphenylphosphonium bromide (0.2 mmol), and the N-phenylphenothiazine hypercrosslinked polymer (6 mg) prepared in Example 4 were added respectively, and 2 mL of N,N-dimethylacetamide was added to the mixture as a solvent. Under 10 W white light irradiation, the reaction was stirred at 25 ° C for 24 hours. The reaction solution was washed with water and extracted with ethyl acetate. The organic layers were combined and dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 100: 1, v / v), 48.8 mg of a white solid was obtained, with a yield of 86% and a melting point of 108-110 ° C.
[0065] 1 H NMR(600MHz,Chloroform-d)δ8.65(dd,J=9.1,5.2Hz,1H),8.54–8.50(m,1H),8 .24–8.19(m,2H),7.81–7.75(m,2H),7.68–7.63(m,1H),7.01(t,J=54.3Hz,1H); 13 C NMR (151MHz, Chloroform-d) δ161.50 (d, J = 249.4Hz), 150.67 (td, J = 26.8, 4.2Hz), 142.24, 130.87, 130.62, 129.16, 129.07, 125. 03 (d, J = 8.4Hz), 124.66, 123.57 (d, J = 9.1Hz), 122.00, 120.70 (d, J = 24.3Hz), 118.36 (t, J = 243.3Hz), 111.32 (dt, J = 22.7, 4.5Hz); 19 FNMR(565MHz,Chloroform-d)δ-110.66,-110.99.
[0066] Application Example 5 Preparation of 6-(difluoromethyl)-8-trifluoromethylphenanthridine
[0067]
[0068] To a 10 mL Schlenk tube equipped with a magnet, 4'-trifluoromethyl-2-isocyano-1,1'-biphenyl (0.2 mmol), difluoromethyltriphenylphosphonium bromide (0.6 mmol), and the N-phenylphenothiazine hypercrosslinked polymer (3 mg) prepared in Example 5 were added respectively, and 2 mL of N,N-dimethylformamide was added to the mixture as a solvent. Under 20 W blue light irradiation, the reaction was stirred at 20 ° C for 12 hours. The reaction solution was washed with water and extracted with ethyl acetate. The organic layers were combined and dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 50:1, v / v), 44.7 mg of a white solid was obtained, with a yield of 75%, and a melting point of 110-112 ° C.
[0069] 1 H NMR(400MHz,Chloroform-d)δ8.86(s,1H),8.75(d,J=8.7Hz,1H),8.58(dd,J=8.1,1.5Hz,1H),8. 23(dd,J=8.0,1.5Hz,1H),8.08(dd,J=8.7,1.8Hz,1H),7.89–7.78(m,2H),7.04(t,J=54.2Hz,1H); 13 C NMR(101MHz,Chloroform-d)δ151.29(t,J=27.0Hz),143.10,135.93,130.94,130.39,129.73(q,J=32.9Hz),129.37,12 7.15(q,J=3.2Hz),125.27,124.09(q,J=4.1Hz),124.03,123.60,122.56,121.72(t,J=2.1Hz),118.26(t,J=243.6Hz); 19 F NMR(376MHz,Chloroform-d)δ-62.43,-109.92.
[0070] Application Example 6 Preparation of 6-(difluoromethyl)-2-methoxyphenanthridine
[0071]
[0072] To a 10 mL Schlenk tube equipped with a magnet, 4'-trifluoromethyl-2-isocyano-1,1'-biphenyl (0.2 mmol), difluoromethyltriphenylphosphonium bromide (0.2 mmol), and the N-phenylphenothiazine hypercrosslinked polymer (3 mg) prepared in Example 1 were added respectively, and 2 mL of N,N-dimethylformamide was added to the mixture as a solvent. Under 10 W purple light irradiation, the reaction was stirred at 40 ° C for 24 hours. The reaction solution was washed with water and extracted with ethyl acetate. The organic layers were combined and dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 25:1, v / v), 39.8 mg of a white solid was obtained, with a yield of 77% and a melting point of 95-97 ° C.
[0073] 1 H NMR(400MHz,Chloroform-d)δ8.64–8.57(m,2H),8.17(d,J=9.0Hz,1H),7.97–7.85(m,2H) ,7.77(t,J=7.7Hz,1H),7.43(dd,J=9.0,2.7Hz,1H),7.08(t,J=54.3Hz,1H),4.06(s,3H); 13 C NMR(101MHz,Chloroform-d)δ159.93,148.83(t,J=26.5Hz),137.52,133.37,131.98,131.00,128 .05,126.60(t,J=4.2Hz),126.49,122.67,122.54,119.34,118.40(t,J=243.5Hz),103.05,55.87; 19 F NMR(376MHz,Chloroform-d)δ-110.16.
[0074] Application Example 7 Preparation of 6-(difluoromethyl)-3-fluorophenanthridine
[0075]
[0076] To a 10 mL Schlenk tube equipped with a magnet, 4-fluoro-2-isocyanate-1,1'-biphenyl (0.2 mmol), difluoromethyltriphenylphosphonium bromide (0.2 mmol), and the N-phenylphenothiazine hypercrosslinked polymer (6 mg) prepared in Example 2 were added respectively, and 2 mL of N,N-dimethylacetamide was added to the mixture as a solvent. Under 30 W blue light irradiation, the reaction was stirred at 25 ° C for 8 hours. The reaction solution was washed with water and extracted with ethyl acetate. The organic layers were combined and dried over anhydrous Na2SO4 and concentrated under reduced pressure. After column separation (the eluent ratio was petroleum ether: ethyl acetate = 100: 1, v / v), 42.5 mg of a white solid was obtained, with a yield of 86% and a melting point of 83-85 ° C.
[0077] 1 H NMR(600MHz,Chloroform-d)δ8.64–8.54(m,3H),7.93(t,J=7.6Hz,1H),7.88(dd,J=9.4 ,2.7Hz,1H),7.77(t,J=7.7Hz,1H),7.53(td,J=8.5,2.7Hz,1H),7.03(t,J=54.3Hz,1H); 13 C NMR(151MHz,Chloroform-d)δ162.87(d,J=249.7Hz),152.75(t,J=26.5Hz),143.78(d,J=11.4Hz),133.81,131.78,127.80,126.75(t,J= 4.2Hz), 124.28 (d, J = 9.4Hz), 122.14, 121.83, 121.98 (d, J = 46.3Hz), 118.20 (t, J = 243.7Hz), 117.95 (d, J = 23.8Hz), 115.19 (d, J = 20.8Hz); 19 F NMR(565MHz,Chloroform-d)δ-110.76,-111.12.
[0078] Experimental Study on the Recycling of N-phenylphenothiazine Hypercrosslinked Polymer Catalyst
[0079] The recycling experiment was based on the reaction described in Application Example 1. After the catalytic reaction was completed, the reaction solution was filtered to obtain N-phenylphenothiazine hypercrosslinked polymer catalyst solid, which was washed with anhydrous ethanol three times and vacuum dried. The obtained solid was then used for the next reaction cycle. Fig. 9 As shown, the N-phenylphenothiazine hyper-crosslinked polymer catalyst can achieve at least 6 cycles of catalysis without obvious loss of catalytic efficiency, indicating that the N-phenylphenothiazine hyper-crosslinked polymer catalyst can be recycled multiple times and has good cyclic stability.
Claims
1. An N-phenylphenothiazine hyper-crosslinked polymer catalyst, characterized in that: The catalyst is a three-dimensional network porous structure hyper-crosslinked polymer material prepared by Friedel-Crafts reaction using N-phenylphenothiazine shown in formula I and dimethylformal shown in formula II as raw materials. The powder X-ray diffraction spectrum of the material has no sharp diffraction peaks, indicating that it lacks crystallinity.
2. The N-phenylphenothiazine hypercrosslinked polymer catalyst according to claim 1, characterized in that: The N2 isothermal adsorption-desorption curve and pore size distribution diagram show that its specific surface area is 305m 2 g -1 The pore size is 2-4 nm; the Fourier transform infrared spectrum shows that its characteristic peak position is 2920 cm -1 、1600cm -1 、1470cm -1 and 1258cm -1 Solid 13 The C CP / MAS nuclear magnetic resonance spectrum shows that the chemical shifts of its characteristic peaks are at 110ppm-150ppm, 55ppm and 40ppm; the thermogravimetric analysis curve shows that the weight loss is 26.0-26.5% at 200-800°C.
3. The method for preparing a N-phenylphenothiazine hypercrosslinked polymer catalyst according to claim 1, characterized in that The method comprises the following steps: utilizing Friedel-Crafts reaction to disperse N-phenylphenothiazine, dimethylol formal and Lewis acid in a solvent, stirring and reacting at 60-120°C for 12-36 hours, cooling and filtering, washing the filter cake with ethyl acetate, dichloromethane and methanol, and then heating and refluxing extraction with methanol in a Soxhlet extractor for 12-24 hours, cooling and filtering again, and drying the obtained solid to obtain an N-phenylphenothiazine hyper-crosslinked polymer catalyst.
4. The method for preparing a N-phenylphenothiazine hypercrosslinked polymer catalyst according to claim 3, characterized in that The molar ratio of N-phenylphenothiazine to dimethylol formal is 1.0:2.0-6.0, the molar ratio of N-phenylphenothiazine to Lewis acid is 1.0:5.0-10.0, and the Lewis acid is at least one selected from titanium tetrachloride, ferric chloride, aluminum chloride, tin tetrachloride, boron trifluoride, iron trifluoromethanesulfonate, and lanthanum trifluoromethanesulfonate.
5. The method for preparing a N-phenylphenothiazine hypercrosslinked polymer catalyst according to claim 3, characterized in that The solvent is selected from at least one of dichloromethane, chloroform, toluene, 1,2-dichloroethane, tetrahydrofuran, 1,4-dioxane, ethanol, and dimethyl sulfoxide, and the dispersion concentration of the N-phenylphenothiazine in the solvent is 0.01-0.1 mol / L.
6. The use of an N-phenylphenothiazine hypercrosslinked polymer catalyst as claimed in claim 1, characterized in that The catalyst is used to catalyze the reaction of a 2-isocyanobiphenyl compound as shown in formula III and difluoromethyltriphenylphosphonium bromide as shown in formula IV to synthesize a 6-difluoromethylphenanthridine derivative as shown in formula V; In Formula III and Formula V, the substituent R 1 , R 2 Each is independently selected from H, C1-C10 alkyl, halogen, C1-C10 alkoxy or aryl, the aryl is selected from phenyl or substituted phenyl, and the substituent on the phenyl ring of the substituted phenyl is C1-C10 alkyl, halogen or C1-C10 alkoxy.
7. The use according to claim 6, characterized in that The 2-isocyanobiphenyl compound shown in formula III, the difluoromethyltriphenylphosphonium bromide shown in formula V and the catalyst are dispersed in a reaction solvent to obtain a reaction solution, and the reaction solution is stirred at 10° C. to 40° C. for 8 to 24 hours under irradiation with a 10-30 W light source, wherein the light source is purple light, blue light or white light. After the reaction, the 6-difluoromethylphenanthridine derivative shown in formula (VI) is obtained by post-treatment.
8. The use according to claim 7, characterized in that The molar ratio of the 2-isocyanatobiphenyl compound shown in formula III to the difluoromethyltriphenylphosphonium bromide shown in formula IV is 1.0:1.0-3.0, and the ratio of the amount of the 2-isocyanatobiphenyl compound shown in formula III to the mass of the catalyst is 1:15-50, the unit of the amount of the substance is mol, and the unit of mass is g.
9. The use according to claim 7, characterized in that The reaction solvent is selected from one of tetrahydrofuran, dichloromethane, acetone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, or any combination thereof, and the dispersion concentration of the 2-isocyanobiphenyl compound shown in formula IV in the reaction solvent is 0.05-0.2 mol / L.
10. The use according to claim 7, characterized in that After the reaction is completed, the post-treatment steps are as follows: the reaction solution is washed with water, extracted with ethyl acetate, the organic layers are combined, dried over anhydrous Na2SO4 and concentrated under reduced pressure, and separated by column chromatography to obtain the target product; The eluent for column chromatography separation is a petroleum ether-ethyl acetate mixture, and the volume ratio of petroleum ether to ethyl acetate is 25-150:1.
Citation Information
Cited By
Method for efficiently preparing ionic super-crosslinked polymer by mechanochemical method, product and application thereof
CN120173216A